Foreword From Editor - 15th Edition - Yatmo, Yandi Andri (ASEAN Journal of Community Engagement, 2024)
In this edition, AJCE thoroughly explores the topic of community engagement programs and their impact, as well as innovative and integrative approaches that highlight their potential to improve the community’s livelihood. This issue features four research articles with unique perspectives on community engagement, one review article that critically evaluates existing approaches, and three case-based articles that explore various concepts further and offer practical insights. The contributors to this edition cover diverse expertise in business and economy, humanity and social sciences, communication, design, and education, presenting a comprehensive range of perspectives on community engagement and its practical implementations.